2011
DOI: 10.1007/s10327-011-0343-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorescent proteins to visualize interactions between the Bakanae disease pathogen Gibberella fujikuroi and the biocontrol agent Talaromyces sp. KNB-422

Abstract: Talaromyces sp. isolate KNB-422, isolated from a rice seedling, is a biofungicidal agent effective against several seedborne pathogens of rice including Gibberella fujikuroi, which causes Bakanae disease. Because the fungal mode of action (MOA) has not yet been clarified, we used the fluorescent protein markers GFP and RFP to visualize cell-cell interactions between the biocontrol agent and the pathogen G. fujikuroi. In slide culture, the hyphal cell wall of G. fujikuroi collapsed, and fluorescence of its cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Furthermore, Th-GFP was observed in the same spots as the pathogen. This fact could be essential for the success of biocontrol, as suggested by Kato et al (2012). Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Th-GFP was observed in the same spots as the pathogen. This fact could be essential for the success of biocontrol, as suggested by Kato et al (2012). Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Using GFP-tagged KNB422 and DsRed2-tagged G. fujikuroi, it was observed that the two fungi occurred in the same part of the rice plant, 18) which indicates that they interact in the plant. erefore interaction between KNB422 and pathogens was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KNB422 grows on rice seeds very rapidly and can also grow well in soil. 13,18) Moreover, the micro ora of the Kureha-soil is usually poor, 13) and, therefore, there may be an ecological niche for KNB422 to occupy the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Trichoderma asperellum SKT-1 (Ecohope®) and Talaromyces flavus SAY-Y-9401 (Tough-block®) are registered as seed treatments for control of seedborne G. fujikuroi (Nagayama et al 2007;Kato et al 2012) and other seed-borne pathogens of rice.…”
Section: Diseases Of Ricementioning
confidence: 99%